Dampak kualitas pelayanan dan kualitas produk terhadap kepuasan konsumen PT. Gemilang Sinar Jaya - Ade Onny Siagian; Hadion Wijoyo (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to determine the effect of product quality and service quality on customer satisfaction PT. Gemilang Sinar Jaya. This study uses a descriptive associative method with a quantitative approach. The population is consumers who made purchases in 2019 as many as 638 consumers and samples taken as many as 86 people. Calculation using SPSS. The results showed that product quality and service quality had a positive effect on customer satisfaction with the regression equation Y = 15.009 + 0.294X1 + 0.422X2. The contribution of product quality, service quality, and customer satisfaction simultaneously is 44.8%, the calculated F value is greater than F table or (39.285> 2,700), with a significance of 0,000 <0,05. There is a simultaneous positive and significant influence between product quality and service quality to customer satisfaction.